Pervaporation separation of isopropanol-water mixtures using crosslinked chitosan membranes with the effect of crosslinker concentrations - Mohd. Rahimi Abd. Wahab, 1989-, author; Hashim Hassan, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - Universiti Teknologi Malaysia, 2012